Isolation and purification of hirudin from local endangered leech species - Ahmad Anwar Mohamed Ismail; Zulhisyam Abdul Kari @ Abdullah; Ibrahim Che Omar (2011)
It has long been known that local leech (Hirudinea sp) contain a substance with anticoagulant properties and the isolation of this was first in 1984 (Weinberg 1994). In this study the purification of the blood-thinning agent hirudin, protein profiling and quantification from different parts of leech body are reported. The result shows the sample from leech head gave the highest result in protein concentration with a value of 69.33 ug/ml compared with the sample from the whole body and headless leech which was 36.67 ug/ml and 26.67 ug/ml, respectively. Sample from leech head was subsequently used for purication by gel permeation chromatography on Sephadex G-75. Fractions which contain significant amounts of protein with absorbance value of more than 0.2 at 595 nm were tested for their anti-coagulant activity on rabbit blood. The result shows that Peak III (fraction number = 23, optical density = 0.256, protein concenntration = 82.00ug/ml) took the longest time for blood to clot (123.33 min) and did not contract but 380 minutes later when compared with Peaks II (fraction number = 21, optical density = 0.293,protein concentration = 94.33 ug/ml) and V (fraction number = 36, optical density = 0.214,protein concentration = 68.00 ug/ml) where clotting was relatively earlier and occurred within13.33 and 23.33 minutes and showed conctraction much sooner at 24.33 and 41.67 minutes later, respectively. Crude protein and eluted fractions which contain significant amount of protein with the longest time of blood to clot were subjected to SDS-PAGE anlysis. The result shows that the molecular weight of hirudin was about 11.36 kDa. From the purification determined by gel permentation chromatographic technique the profiles of leech crude extract from different parts of body indicated that the anti-coagulant agent or hirudin is only found in substantial quantities in the head (salivary glands) of leeches.